ACTIVITY OF FREE-RADICAL OXIDATION IN LUNGS OF RATS АТ EXPERIMENTAL BURN DISEASE - Sukhomlyn Т.A.; Netуukhaylo L.G. (World of Medicine and Biology, 2012)
Under conditions of burn disease pathological changes in lungs tissues oppear in result of the аctivation of free-radical oxidation. In article there are dates about increasing of level of middle molecules (MM), malondialdehyde (MDA), oxidative modification proteins (OMP) in lungs of rats with burn disease.